Optimizing Digital-Based Measuring Tools in Evaluation of Balinese Language Learning at SMP Negeri 11 Denpasar - Ni Putu Diana Sari; Ida Bagus Putrayasa (CV. Creative Tugu Pena, 2024)
This study aims to describe the efficiency and relevance of optimizing the effectiveness of digital-based assessment tools for evaluating Balinese language learning at SMP Negeri 11 Denpasar. This issue arises from the fact that teachers at SMP Negeri 11 Denpasar have not yet utilized digital-based assessment tools optimally. This is reflected in the Balinese language learning evaluation activities, where teachers tend to rely on conventional assessment tools or are limited to using a single digital tool, such as Google Forms, which affects students' learning outcomes. The implementation of this study is based on the use of a method as an operational foundation. Accordingly, the study addresses (1) research design, (2) types of research data, (3) data collection methods, and (4) data analysis methods. The results indicate that efficiency includes ease of implementation in evaluation processes. Meanwhile, relevance involves the capability of digital assessment tools to provide evaluations aligned with the needs of the learning process.